PENGUATAN GURU DALAM PENYUSUNAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS QUIZZIZ DI SD MUHAMMADIYAH 29 SUNGGAL KAB. DELI SERDANG - Elfrianto Elfrianto; Eko Febri Syahputra Siregar; Lilik Hidayat Pulungan; Nur'Afifah Nur'Afifah; Ismail Hanif Batubara (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This activity is entitled Strengthening teachers in preparing quizziz-based student worksheets at SD Muhammadiyah 29 Sunggal, Deli Serdang Regency. The purpose of this activity is to provide reinforcement for teachers at SD Muhammadiyah 29 in implementing learning during the Covid-19 pandemic. The strengthening in question is training and assistance in the management of Quizziz-assisted evaluation. This needs to be done in order to improve the quality of education in schools which are part of the Muhammadiyah organization's charitable efforts. The method used in this activity is training with the steps of preparation, implementation and evaluation. The success of this activity is not only on the teacher's understanding of using the Quizziz application during training, but is the application in each class to increase students' interest and motivation to learn.